تحليل العوامل المعسر فى قراءة النصوص العربية لطلاب الفصل الحادي عشر فى المدرسة العالية الإسلامية بمعهد"مفتاح الإصلاح تمبيلوك ماترام - suparmanto suparmanto; Ruwaida Hudatullah; Fikri Haikal (Ihtimam : Jurnal Pendidikan Bahasa Arab, 2021)
Abstract :This study discussed the analysis factors of students’ difficulty in reading Arabic texts for eleventh-grade students at MA MiftahulIslahTembelok, Mataram, for the academic year of 2020/2021. This study aimed to explore the Arabic Language instructional processes, especially Qira’ah; examined the factors that influenced students’ difficulty in reading Arabic text; as well as find out the solutions to overcome thosedifficulties.This descriptive qualitative study adopted the observation, interview, and documentation method to collect the data. The observation method is used to obtain the information by observing the instructional processes of Arabic language learning, especially for the Qira'ah section, what methods are used during the learning processes, observing the difficulty factors, and revealing the solutions. Meanwhile, the interview method is used to obtain the data and information related to difficulty factors in reading Arabic text. Furthermore, the documentation method is used to collect the data and information related to the MA MiftahulIslahTembelokoverview.This current study revealed that there was a significant result where there were more students who are able to read Arabic texts compared to students who have difficulty. However, the teacher keep motivates, guides, and boost students’ confidence in order to get better results.